The Tension between Religion and Democracy - Herry-Priyono, B. (Masyarakat: Jurnal Sosiologi, 2017)
The growing revival of religious sentiments in the past few decades exposes serious faults in the explanatory power of the so-called modernization theories, urging social scien- tists to seek new avenues in understanding the phenomena. The article focuses on the way the present character of religious fundamentalism needs to be understood not as a form of traditionalism but as one of the springboard effects inseparable from hybrid modernity. In particular, it highlights the tension between religious fundamentalism and democracy as revolving around at least two points. One is the antinomy between diver- sity as the sine-qua-non of democracy and the absolutist tendency of fundamentalist beliefs, and the other a collision between the secular and sacral conceptions of sovereignty. By learning from the debates on the place of religion in the public sphere, the article outlines some points for the prospect of co-existence between religion and democracy.